Impact Analysis and Prevention of Learning Saturation - Sarah Nofis A’raaf; Muhibbin Syah; Bambang Samsul Arifin (al-Afkar, Journal For Islamic Studies, 2024)
Learning saturation is a syndrome where a person experiences extreme fatigue and boredom, which makes them feel uninspired in doing learning activities . The type of research used is qualitative descriptive. Descriptive research signifies that researchers are trying to describe a phenomenon or event. The purpose of this article is to discuss learning burnout, including its effects, how to prevent it, and strategies for doing so. According to the study's findings , monotonous learning is usually caused by a long and tedious learning process . New learning environments and goals and motivations to inspire learners to work more than ever are two ways to overcome learning burnout.